State Responsibility in Providing Legal Protection against Child Victims of Sexual Violence - Mangesti, Yovita Arie; Dharmawan, I Komang Aries (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The background of this study discusses the state's responsibility to provide legal protection for children who have been sexually abused, while social norms still reveal the blurred norms between the rules and the implementation. The problem problem with this study is the urgency of the state's responsibility to provide legal protection to child victims of sexual abuse and state responsibility to provide legal protection against child abuse. The approach method used in this study is a normative-law study, which is a study that examines law regulations, legal principles, and also a theory or doctrine of law. The study also employed a constitutional approach and a case approach. The conclusion of this study is the rights of children who are victims of criminal ACTS accommodated by 2017 government government regulation no. 43 year 2017 on the implementation of restitution to children who are victims of criminal crimes, and there is yet another flawless flaw in the forced efforts of the implementation of restitution by the perpetrator to the child who has committed the crimes, If the perpetrator fails to render a court ruling of consistent force.